Spleen tyrosine kinase: a novel pharmacological target for sepsis-induced cardiac dysfunction and multi-organ failure - Verra, Chiara; Paulmann, Maria Kerstin; Wegener, Jamila; Marzani, Enrica; Ferreira Alves, Gustavo; Collino, Massimo; Coldewey, Sina Maren; Thiemermann, Christoph (Frontiers in Immunology, 2024)
Sepsis is a systemic condition caused by a dysregulated host response to infection and often associated with excessive release of proinflammatory cytokines resulting in multi-organ failure (MOF), including cardiac dysfunction. Despite a number of effective supportive treatments (e.g. ventilation, dialysis), there are no specific interventions that prevent or reduce MOF in patients with sepsis. To identify possible intervention targets, we re-analyzed the publicly accessible Gene Expression Omnibus accession GSE131761 dataset, which revealed an increased expression of spleen tyrosine kinase (SYK) in the whole blood of septic patients compared to healthy volunteers. This result suggests a potential involvement of SYK in the pathophysiology of sepsis. Thus, we investigated the effects of the highly selective SYK inhibitor PRT062607 (15mg/kg; i.p.) on sepsis-induced cardiac dysfunction and MOF in a clinically-relevant, murine model of sepsis. PRT062607 or vehicle (saline) was administered to 10-weeks-old C57BL/6 mice at 1h after the onset of sepsis induced by cecal ligation and puncture (CLP). Antibiotics (imipenem/cilastatin; 2mg/kg; s.c.) and analgesic (buprenorphine; 0.05mg/kg; i.p.) were administered at 6h and 18h post-CLP. After 24h, cardiac function was assessed in vivo by echocardiography and, after termination of the experiments, serum and cardiac samples were collected to evaluate the effects of SYK inhibition on the systemic release of inflammatory mediators and the degree of organ injury and dysfunction. Our results show that treatment of CLP-mice with PRT062607 significantly reduces systolic and diastolic cardiac dysfunction, renal dysfunction and liver injury compared to CLP-mice treated with vehicle. In addition, the sepsis-induced systemic inflammation (measured as an increase in inflammatory cytokines and chemokines in the serum) and the cardiac activation of NF-kB (IKK) and the NLRP3 inflammasome were significantly reduced in CLP-mice treated with PRT062607. These results demonstrate, for the first time, that SYK inhibition 1h after the onset of sepsis reduces the systemic inflammation, cardiac dysfunction and MOF, suggesting a potential role of the activation of SYK in the pathophysiology of sepsis. Novel therapeutic strategies that inhibit SYK activity may be of benefit in patients with diseases associated with local or systemic inflammation including sepsis.